Writing Great Fiction: Storytelling Tips and Techniques - James Hynes (THE GREAT COURSES, 2023)
We all think we have a novel in us, and in this course of 24 lectures, a professional novelist will guide you through a survey of the most important concepts and techniques behind the creation of novels and stories, as well as some demonstrations of his own process. By taking you step by step through such topics as creating characters, composing dialogue, crafting plots, and using different points of view, this course will help you get that book out of your head and heart and into the hands of readers.